Corona Virus Disease 2019 (COVID-19) Prevention and Control Measures in Community: A Literature Review - Kalikotay, Bhagawaty (Rupantaran: A Multidisciplinary Journal, 2020)
There is a new public health crises threatening the world with the emergence and spread of 2019 novel coronavirus (2019-nCoV) or the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). There have been around 25,300,975 reported cases of coronavirus disease 2019 (COVID-2019) and 848,673 reported deaths to date (30/08/2020). Extensive literature review of publicly available information to summarize sign and symptoms as well as prevention of COVID-19 was carried out. The disease is transmitted by inhalation or contact with infected droplets and the incubation period ranges from 2 to 14 days. The symptoms are usually fever, cough, sore throat, breathlessness, fatigue, malaise among others. The disease is mild in most people; in some (usually the elderly and those with comorbidities), it may progress to pneumonia, acute respiratory distress syndrome (ARDS) and multi organ dysfunction. Many people are asymptomatic. The case fatality rate is estimated to range from 2 to 3%. Diagnosis is by demonstration of the virus in respiratory secretions by special molecular tests. Common laboratory findings include elevated C-reactive protein (CRP). Prevention entails home isolation of suspected cases and those with mild illnesses and strict infection control measures at hospitals that include contact and droplet precautions.